2015
DOI: 10.1063/1.4921325
|View full text |Cite
|
Sign up to set email alerts
|

Random laser emission in a sphere-phase liquid crystal

Abstract: We investigated random lasing from a fluid self-assembly sphere-phase liquid crystal, which was composed of three-dimensional twist sphere structures with disclinations among them. The threshold energy of the random lasing from sphere-phase liquid crystal was 32% of that from the chiral nematic phase because of the interference associated with multiple scattering by randomly distributed sphere-phase platelets. Such random lasers composed of self-assembly soft organic materials may be useful for holographic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…We have also demonstrated that tiny aggregates of the AIE dye were still capable of giving out strong emissions, thus changing the limitations associated with low solubility of dyes or liquid crystals containing small amount of defects into advantages. AIE dyes are promising gain media for a variety of laser hosts that possess topological defects such as blue phase [25,26] and "sphere phase" liquid crystals [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…We have also demonstrated that tiny aggregates of the AIE dye were still capable of giving out strong emissions, thus changing the limitations associated with low solubility of dyes or liquid crystals containing small amount of defects into advantages. AIE dyes are promising gain media for a variety of laser hosts that possess topological defects such as blue phase [25,26] and "sphere phase" liquid crystals [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we demonstrate a tunable NIR filter based on sphere phase liquid crystal (SPLC). The sphere phase, usually observed between the isotropic phase (Iso) and chiral nematic phase (N*) or between the isotropic phase and blue phase, has been demonstrated by Jiliang Zhu [15][16][17][18]. Like the BPLC, the SPLC is composed of self-assembly periodic helical structures and disclinations among them, as shown in Figure 7 [15].…”
Section: Introductionmentioning
confidence: 94%
“…Random laser action occurs from multiple scattering of light in disordered systems [1], in which light propagating in a closed loop path in an active medium is amplified [2,3]. Since random lasers do not require any external optical resonators, they have raised attention as easy-to-make, low-cost and speckle-free lasers advantageous for applications in imaging [4], photonics [5] and biomedicine [6,7]. Meanwhile, in general, the light paths of random lasers are so chaotic that their mode control is difficult [8].…”
Section: Introductionmentioning
confidence: 99%